The harmonization of small-scale marine spatial protection in the Argentine Islands area (Antarctic Peninsula) under the Antarctic Treaty System - A. Fedchuk; O. Sinna; G. Milinevsky; A. Utevsky (Ukrainian Antarctic Journal, 2020)
The purpose of the article is to summarize the results of field studies carried out in the framework of the State Antarctic Research Program for 2011–2020 and undertaken to identify areas of special interest for small-scale marine spatial protection in the Argentine Islands water area. The scientific results reported in the publications and relevant meetings’ documents officially presented by the Ukrainian delegation in 2012–2019 were summarized and interpreted in view of the Antarctic Treaty System (ATS) provisions on marine spatial protection. GIS analysis was applied to field data. It is shown that the development of protection regime for small-scale underwater landscape is based on systematic biogeographical data collected during seasonal and year-round Ukrainian Antarctic expeditions in 2011–2019. In order to harmonize the application of all available tools of spatial ecosystem-based protection across the ATS, it is proposed to designate the long-term environmental monitoring sites around Ukrainian Antarctic Akademik Vernadsky station as a new Antarctic Specially Protected Area (ASPA) consisting of terrestrial and marine components. It is shown that the marine component of the proposed ASPA could serve as one of the scientific reference areas of the broad-scale Marine Protected Area in Domain 1 within the Antarctic Peninsula region for assessing the impact of climate change on benthic communities, as well as breeding success and distribution of penguin colonies.